Halal Certification Training as an Effort to Increase Customer Satisfaction in the Start-Up Business of UNUSA Students - Rachma Rizqina Mardlotillah; Endah Budi Permana; Denis Fidita Karya; Riyan Sisiawan Putra; Hidayatul Khusnah; Mohamad Rijal Iskandar Zhulqurnain; Pance Mariati (Community Development Journal, 2022)
Lack of understanding regarding halal label certification in a start-up business within the Nahdlatul Ulama University Surabaya is an obstacle in implementing halal product guarantees for a product or service. If further researched, halal certification on a product, especially in a start-up, will affect customer satisfaction and increase the profits of a business. Therefore, this community service activity aims to provide literacy and training about a halal certification to increase customer satisfaction in the Unusa Student Start-Up business. This community service activity targets 26 students of Nahdlatul Ulama University Surabaya who have a start-up business. The method used is lecture and question and answer. Meanwhile, the evaluation of activities is carried out by distributing questionnaires regarding knowledge related to halal certification and customer satisfaction, which is then analyzed using Paired Sample Test. The results obtained are a significant increase in knowledge (p-value 0.000). This is evidenced by the average knowledge score before training of 3.83 to 5.42 after training. After this training, students hope to get further assistance related to halal certification in start-up businesses